Realisation and Characterisation the BEC for 87Rb Atoms (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The Bose-Einstein condensate (BEC) is created in a magnetic trap in the Quadrupole-Ioffe configuration (QUIC). This kind of trap combines an anti-Helmholtz quadrupole field with an offset field produced by a single coil perpendicular to the quadrupole field axis to suppress Majorana transitions. In the quadrupole trap evaporative cooling is performed by using radio frequency, reaching the phase transition to a BEC in the QUIC trap. By using Time of Flight (TOF) technique, the expansion velocity is measured with  and  which lead to temperature of  and  It is roughly around the recoil temperature.